(untitled) (Journal of actual problems of jurisprudence, 2018)
The article describes a class of environmental impact assessments carried out in the sphere of environmental protection under the laws of the Republic of Kazakhstan. The differences forensic environmental impact assessments from other examinations. Noted any examination included in the class. A brief description of objects forensic environmental impact assessments, based on the data of the natural sciences. Key words: ecology, environmental offenses, crime, evidence, experts, specialists, soil, air, water.